Workplace harassment/violence and job outcomes: its consequences among female employees in the higher education sector - Khaliq, Abidah; Ali Mohamed, Ashgar Ali; Ahmad, Muhammad Hassan (Lexis Nexis Malaysia Sdn Bhd, 2021)
This study will contribute to the understanding of workplace violence and its influence on the key work outcomes in the education sector in the context of Pakistan through the buffer role of legal environment.